Growth and development of children living in incarceration environments of the province of Buenos Aires, Argentina - Di Iorio, Susana (2019)
Objective: The objective of this study was to examine the nutritional status, psychomotor and socioemotional development of children living with their mothers in prison in the province of Buenos Aires, Argentina.Material and method: Sex, age, weight and height were measured in children (37) residing with their mothers (28) in Prison No. 33 of the SPB. Nutritional indicators were calculated and analyzed according to the WHO international reference (2006). National Research Test (PRUNAPE) and the parental questionnaire Ages and Stages Questionnaires: Socio-Emotional®, Second Edition (ASQ:SE-2) were applied to evaluate development.Results: Anthropometric evaluation showed that 7of children under 2 years presented low weight, 3alert of low weight, 28high weight and 14low height. Children over 2 years of age showed 37.5of high weight and 25of risk of overweight. There were no children with short stature. PRUNAPE and ASQ:SE-2 tests: in the 30 cases that completed both tests more than half (53.3) obtained scores within the expected range. In the group of children with both tests who did not pass the PRUNAPE (n = 9), the result found in the ASQ-SE 2 was diverse: 66.6within expectations and 33.3at risk. Neither of children with both tests who did not pass the ASQ:SE-2 passed the PRUNAPE.Conclussion: There were high prevalences of excess weight and high percentages of risk in psychomotor development, considerably higher than in the general population. There is a need to take action to reduce the harmful effect of childhood confinement.